Treatment effects of a Twin-Force Bite Corrector versus an Activator in comparison with an untreated Class II sample: a preliminary report - Dalci Oyku; Altug Ayse Tuba; Memikoglu Ufuk Toygar (Sciendo, 2014)
Objectives: The present study aimed to compare the treatment outcomes of a fixed-functional appliance (Twin-Force Bite Corrector - TFBC) and a conventional removable functional appliance (Activator) in the treatment of skeletal Class II malocclusions.